2011
DOI: 10.1038/leu.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

Escalation of daunorubicin and addition of etoposide in the ADE regimen in acute myeloid leukemia patients aged 60 years and older: Cancer and Leukemia Group B Study 9720

Abstract: Untreated de novo (n=421) and secondary (n=189) acute myeloid leukemia (AML) patients≥60 years received intensified chemotherapy, including daunorubicin 60mg/m2 and etoposide 100mg/m2 during days 1, 2, 3 with cytarabine 100mg/m2 during days 1–7, with a second induction if needed and one consolidation course with these drugs and doses for 2, 2 and 5 days, respectively. In all, 287 (47%) achieved complete remission (CR), 136 (22%) died and 187 (31%) were non-responders. CR rates were 27, 44 and 52% for complex k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Other studies have reported response rates of 46% (6/13 patients) [27], 50% (3/6 patients) [36], and 62% (8/13 patients) [37]. The CR rates for patients with secondary AML in general (evolved from either MDS or MPD) are reported to be in the range of 30-60% [38][39][40][41]. The data reported here, combined with limited data from the literature, suggest that a significant percentage of patients with MPN-BP can achieve CR or CP after induction chemotherapy, and may thus be candidates for allo-SCT.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have reported response rates of 46% (6/13 patients) [27], 50% (3/6 patients) [36], and 62% (8/13 patients) [37]. The CR rates for patients with secondary AML in general (evolved from either MDS or MPD) are reported to be in the range of 30-60% [38][39][40][41]. The data reported here, combined with limited data from the literature, suggest that a significant percentage of patients with MPN-BP can achieve CR or CP after induction chemotherapy, and may thus be candidates for allo-SCT.…”
Section: Discussionmentioning
confidence: 92%
“…Although essentially all patients received anthracycline and cytarabine-based induction therapy, multiple postremission therapies were administered. [16][17][18][19][20][21][22][23] Additionally, supportive care for AML patients undergoing intensive therapy has improved in the last 2 decades.…”
Section: Discussionmentioning
confidence: 99%
“…21 CALGB 9420 (phase 1) and CALGB 9720 (phase 3) evaluated multidrug resistance modulation by PSC-833 during induction and consolidation therapy with cytarabine, daunorubicin, and etoposide, but the PSC-833 arm was closed after random assignment of 120 patients because of a high number of early deaths. 22,23 Enrollment continued for patients on the chemotherapy-only control arm. Postremission therapy consisted of a single cytarabine, daunorubicin, and etoposide consolidation course also with PSC-833 until arm closure and the patients were subsequently randomly assigned to receive or not rIL2 maintenance therapy similar to CALGB 19808.…”
Section: Cytogenetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive induction is effective in selected octogenarian acute myeloid leukemia patients: prognostic significance of karyotype and selected molecular markers used in the European LeukemiaNet classification 27 6 patients) and low-dose chemotherapy (CALGB 8923 and 9720, 27,29 BGMT 95 24 and ALFA 9803, 30 for a total of 9 patients]. Three patients on AMLCG 99 also received maintenance chemotherapy.…”
Section: Introductionmentioning
confidence: 99%